The Effect of Capital Structure, Sales Growth, Cash Turnover, and Firm Size on Profitability Mediated by Operational Effiency: Evidance from Healthcare Industry Listed on IDX - Syofyan, Hamad; Fitra, Halkadri (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the effect of capital structure, sales growth, cash turnover, and firm size on profitability mediated by operational efficiency in Indonesia’s healthcare industry listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The healthcare sector is a capital-intensive industry that faces high operational costs and complex regulations, leading to fluctuating profitability despite strong sales growth. This topic is relevant because previous studies provide inconsistent findings regarding the relationship between leverage and profitability in capital-intensive firms. The research adopts a quantitative approach using secondary data from financial statements of healthcare companies listed on IDX. Samples were selected through a purposive sampling technique, and panel data regression with the Fixed Effect Model (FEM) was used for hypothesis testing. Operational efficiency was analyzed as a mediating variable through the Sobel test to examine indirect effects. The findings of this study indicate that capital structure (DER) and firm size have a significant negative effect on operational efficiency. However, capital structure does not significantly affect profitability (ROA), while firm size has a significant negative effect on profitability (ROA). The results also show that sales growth and cash turnover have no significant effect on operational efficiency. Furthermore, operational efficiency is proven to mediate the negative and significant effects of capital structure and firm size on profitability (ROA), but it does not mediate the relationship between sales growth and cash turnover with profitability (ROA).These findings imply that healthcare companies should optimize their capital structure and asset utilization while enhancing operational efficiency to sustain profitability.